Photosensitization mechanism of algogenic extracellular organic matters (EOMs) in the photo-transformation of chlortetracycline: Role of chemical constituents and structure. (1st November 2019) - Tian, Yajun; Wei, Lianxue; Yin, Ze; Feng, Li; Zhang, Lirong; Liu, Yongze; Zhang, Liqiu
Abstract: The ubiquitous algogenic extracellular organic matters (EOMs) could enhance solar photodegradation of antibiotics such as Chlortetracycline (CTC), however, the role of chemical constituents and structure in their photosensitizing process was not clear. In this paper, EOMs were extracted from chlorella vulgaris (CV-EOMs), scenedesmus meyen (SM-EOMs) and microcystis aeruginosa (MA-EOMs) to explore their photosensitive efficiencies and mechanisms. All of the EOMs showed higher photosensitive efficiencies than natural organic matter (NOM). The quenching assays and competitive kinetics experiments confirmed the dominant role of 3 EOMs* in accelerating CTC photodegradation. The quantum yield coefficients of 3 EOMs* ( f TMP ) of CV-EOMs, SM-EOMs, MA-EOMs, NOM were 139.89 ± 5.46, 125.35 ± 4.69, 91.76 ± 3.53, and 72.84 ± 4.45 L/(mol-photon), respectively. Specific chemical constituents and structure of EOMs were characterized by nuclear magnetic resonance (NMR), fourier transform ion cyclotron resonance mass spectrometry (FT-CIR-MS) and X-ray photoelectron spectroscopy (XPS). The results showed the positive linear correlation of f TMP with content of carbonyl groups in EOMs. In addition, reduction of carbonyl groups in EOMs by NaBH4 significantly decreased CTC photodegradation rate. Density Functional Theory (DFT) calculation suggested the susceptible excitation of carbonyl groups in EOMs under solar light was ascribed to the lowest required energy of electronic transition from HOMO to LUMO (assigned as n-π* transition). The energy of triplet excited-states benzophenone, p-methoxy acetophenone and acetophenone (the EOMs model compounds) was calculated to be 284.92, 288.85 and 265.50 kJ/mol, which were higher than that of CTC (i.e., 217.46 kJ/mol), indicating the energy transfer from excited triplet state to excited triplet state CTC was possible. This study provided mechanism insights into photosensitization effects of allogenic EOMs on photochemical fate of pollutants in aqueous environment. Graphical abstract: Image 1 Highlights: EOMs derived from three algae could significantly accelerate the CTC photolysis. Triplet state EOMs ( 3 EOMs*) was confirmed to be the dominant reactive species. The carbonyl groups were quantified through combining FT-ICR-MS with XPS. The positive correlation of f TMP with contents of carbonyl groups was observed. The energy transfer from 3 EOMs* to CTC was possible based on DFT calculation.